Geochemistry on pryite concretions from the Romanche Trench - Enrico Bonatti; B-M Honnorez-Guerstein; Jose J Honnorez; C Stern (PANGAEA, 1976)
Pyrite concretions a few centimeters in diameter were recovered from within the east-west valley of the Romanche fracture zone (equatorial Atlantic). Unconsolidated sediments are scarce or absent in this area of the Romanche Valley. Some of the sulfide concretions were transformed into Fe hydroxides by the action of seawater. The major element, trace metal, rare earth element and sulfur isotopic chemistry of these concretions suggest that they were deposited from Fe- and S-bearing hydrothermal solutions at or beneath the seafloor. These findings support the hypothesis that oceanic fracture zones are the locus of metallogenesis. Heat flow patterns suggest deep sub-seafloor hydrothermal circulation in the highly fractured offset zones. Metals and sulfur can be extracted by the hydrothermal waters from rocks present beneath the fracture zone (basalt, gabbro and serpentinite) and can also be supplied by mantle volatile sources. Important metal deposits appear to be aligned along the predrift land extension of some oceanic fracture zones.
Supplement to: Bonatti, E et al. (1976): Hydrothermal pyrite concretions from the Romanche trench (equatorial Atlantic): metallogenesis in oceanic fracture zones. Earth and Planetary Science Letters, 32(1), 1-10, https://doi.org/10.1016/0012-821X(76)90177-1